2022
DOI: 10.2217/pgs-2022-0077
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA MALAT1 Regulates the Resistance of Breast Cancer Cells to Paclitaxel Via the miR-497-5p/ SHOC2 axis

Abstract: Aim: To explore the roles of lncRNA MALAT1 and SHOC2 in breast cancer, and the potential connections to chemotherapy resistance in breast cancer. Materials & methods: Paclitaxel-resistant breast cancer cells were induced by gradually increasing intermittent doses. Bioinformatic analyses were performed to predict the regulated miRNAs of MALAT1. Results: High expressions of MALAT1 and SHOC2 contribute to paclitaxel resistance in breast cancer cells. MALAT1 sponges miR-497-5p enhance SHOC2 expression in pacli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…37,38 Upregulation of miR-497-5p improves the treatment response of patients with BC to paclitaxel by repressing MALAT1 and SHOC2. 39 In our study, the miR-497-5p expression level in cancer tissues was furthermore proved as an independent risk factor affecting death in patients with BC.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…37,38 Upregulation of miR-497-5p improves the treatment response of patients with BC to paclitaxel by repressing MALAT1 and SHOC2. 39 In our study, the miR-497-5p expression level in cancer tissues was furthermore proved as an independent risk factor affecting death in patients with BC.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, overexpression of miR-497-5p is devoted to the downregulation of tumoral programmed death ligand-1 expression in triple-negative breast cancer and suppression of triple-negative breast cancer development 37,38 . Upregulation of miR-497-5p improves the treatment response of patients with BC to paclitaxel by repressing MALAT1 and SHOC2 39 . In our study, the miR-497-5p expression level in cancer tissues was furthermore proved as an independent risk factor affecting death in patients with BC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lncrna malat1 can promote doxorubicin resistance in breast cancer by regulating mir‐570‐3p 15 . Meanwhile, lncrna malat1 could also promote the resistance of breast cancer cells to paclitaxel via mir‐497‐5p/shoc2 axis 16 . These studies suggest that lncRNAs may promote or suppress chemoresistance and drug sensitivity in related cancers.…”
Section: Introductionmentioning
confidence: 84%
“…15 Meanwhile, lncrna malat1 could also promote the resistance of breast cancer cells to paclitaxel via mir-497-5p/shoc2 axis. 16 These studies suggest that lncRNAs may promote or suppress chemoresistance and drug sensitivity in related cancers. It has been shown that Miat can affect cisplatin resistance in non-small cell lung cancer by regulating miRNA.…”
mentioning
confidence: 99%
“…BC is a multifaceted disease that develops and progresses due to several genetic and molecular changes [ 176 , 177 ]. MALAT-1 is one example of a molecule that has recently attracted much interest [ 178 , 179 ]. In a recent study, Ou and colleagues sought to determine the relationship and clinicopathological importance of two biomarkers, MALAT-1 and the transcription factor BTB and CNC homology 1 (BACH1), in TNBC [ 180 ].…”
Section: Reproductive Cancersmentioning
confidence: 99%